Strengthen PSNP Institutions and Resilience Phase II (SPIR II), Ethiopia: Baseline Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset is part of the IMPEL (Implementer-Led Evaluation and Learning) evaluation of SPIR-II (Strengthen PSNP Institutions and Resilience), a randomized controlled trial launched in 2022. The SPIR-II aims to enhance livelihoods, increase resilience to shocks, and improve food security and nutrition for rural households vulnerable to food insecurity in Ethiopia.